Price Fluctuations in Econophysics - Ulusoy, Tolga (Springer International Publishing, 2017)
The object of this research is to produce perspective to deal with the challenge that can surpass boundaries and limitations of scientific acceptance of the theory in social sciences and economics. The main spots of activity in Econophysics has been the financial markets, and having to accept the stock market as a complex network of natural events for physicists by navigating through its terabytes of well-defined time series data. The evidence for the fat-tailed distribution of asset price changes has now been established beyond doubt as a truly universal feature of economic souk. Field of Physics consists of theoretical foundations of several types of research, obtained through multi-disciplined instruction that can help make scientific and objective experiments with reference to predictive facts. As a result of this, the required experiments could administrate in different areas.
Keywords: 8. Economic growth